(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: Detection of iron deficiency early during pregnancy is essential for correct management. Red cell distribution width (RDW) is a new routine parameter in fully automated hematology analyzer that can give the idea of early iron deficiency before Hb%. This study was aimed to see the role of red cell distribution width and Hb% in determining early iron deficiency in pregnant women. Methods: In this study 190 pregnant women were included. CBC including Hb% and RDW and iron profile were done. RDW were compared with Hb% in various stages of iron deficiency. Results: RDW was more significant than Hb level in latent iron deficiency when Hb level was normal (p<0.05). In mild and moderate iron deficiency anemia, RDW was increased progressively though Hb level was reduced. In this study RDW had sensitivity 82.3% and specificity 97.4%. Whereas Hb level had sensitivity 56.6% and specificity 90.9% for iron deficiency. Conclusion: Latent iron deficiency without other complicating disease could be screened out early by increased RDW when Hb% was normal. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 137-141